THE EFFECT OF PROFESSIONALISM, LEADERSHIP STYLE, AND ORGANIZATIONAL COMMITMENT ON AUDITOR PERFORMANCE (Empirical Study at the Representative Office of the Financial and Development Supervisory Agency of Riau Province) - Haniva, Ray; Sosiady, Mulia; Djamil, Nasrullah (International Journal of Business and Information Technology, 2025)
This study aims to determine the effect of professionalism, leadership style, and organizational commitment on auditor performance at the Representative Office of the Financial and Development Supervisory Agency of Riau Province. The population in this study were auditors working at the Representative Office of the Financial and Development Supervisory Agency of Riau Province. The sampling technique used saturated sampling so that the total sample was 35 auditors. Data analysis used the classical assumption test and hypothesis testing using SPSS20. The results showed that professionalism and organizational commitment had a significant effect on auditor performance. Meanwhile, leadership style did not affect auditor performance. The results of the R-Square test showed that the independent variables used in this study could explain the dependent variable by 67.3% while the remaining 32.7% was influenced by other variables not examined in this study such as audit structure variables, work motivation, emotional intelligence, locus of control, and others.